Many-Body Potential for Point Defect Clusters in Fe-C Alloys - Lau, T.; Forst, C.; Lin, X.; Gale, Julian; Yip, S.; Van Vliet, K. (The American Physical Society, 2007)
Modeling the consequences of crystalline defects requires efficient interaction sampling. Empirical potentials can identify relevant pathways if the energetics and configurations of competing defects are captured. Here, we develop such a potential for an alloy of arbitrary point defect concentration, body-centered cubic -aFe supersaturated in C. This potential successfully calculates energetically favored defects, and predicts formation energies and configurations of multicarbon-multivacancy clusters that were not attainable with existing potentials or identified previously via ab initio methods.